2006
DOI: 10.2355/isijinternational.46.1533
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Behaviour of Oxide Scale in Hot Rolling

Abstract: In the hot strip mill, the slab is brought to temperature in the reheating furnace and discharged for rolling. To break the primary scale, the slab is passed through a slab descaler before the reversing roughing mill. A secondary oxide scale is inevitably formed between successive rolling passes during hot rolling, which is further removed by high pressure water jets before the subsequent passes during reversing rolling or before the strip enters the tandem finishing mill. Whether the oxide scale is deformed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…It is known this oxide can deform plastically in hot rolling [9,10,13,14,16,17]. Probably, similar phenomenon occurred in this hot forging test.…”
Section: Investigation Of Dent Defectsmentioning
confidence: 77%
See 1 more Smart Citation
“…It is known this oxide can deform plastically in hot rolling [9,10,13,14,16,17]. Probably, similar phenomenon occurred in this hot forging test.…”
Section: Investigation Of Dent Defectsmentioning
confidence: 77%
“…Moreover, reducing environmental emission from lubrication processes for metal forming is also required [8]. Thus, in hot rolling and hot stamping a lot of good research works have given very useful information [9][10][11][12][13][14][15]. In hot forging, however, threre were not many research works on tribology.…”
Section: Introductionmentioning
confidence: 99%
“…This is same as the result that Krzyznowski et al reported. 15) The value is in the range from 1 MPa to 2 MPa. It is worthwhile to note that the values are quite small than those obtained by Kushida et al.…”
Section: Nucleation Conditionmentioning
confidence: 99%
“…[14][15][16][17][18] In this model, the cracks are assumed to preexist in the oxide scale, and no new cracks form during hot rolling. …”
Section: Fem Modelmentioning
confidence: 99%